Understanding the Labor Market Decisions and Outcomes of Nepal's Young Adults - World Bank (World Bank, Washington, DC, 2018)
Promoting early labor market success of workers has increasingly become an important economic and social development aim internationally, as exemplified by the 2030 United Nations (UN) Sustainable Development Goals related to youth employment. Many low-income countries, including Nepal, are in the middle of a youth bulge in their demographic structure. In addition, today’s youth in Nepal are, on average, more educated than past generations. These developments present real opportunities for the country. Nepal also faces risks from failing to provide sufficient, appropriate employment which is productive and remunerative to youth. International evidence suggests that the labor market challenges and behaviors of youth differ in important ways from those of the overall adult population. For example, the youth labor market outcomes are more likely to be hurt or youth are more likely to migrate out when local economic conditions are weak or deteriorate. Youth face additional barriers to labor market integration due to their relative lack of labor market experience and access to social, financial, and physical capital to establish and run their own income generating activities. Youth’s exposure to weak labor market conditions, even if the conditions are short lived, can lead to long-lasting, adverse labor market and economic outcomes over their working lives. Systematic, policy-oriented empirical research on labor and livelihoods in Nepal is limited, however. Dedicated examinations of the labor market behavior of young adults are rarer still. The literature tends to be composed of sociological studies of Nepal’s labor history, intertwined with the country’s social and political history; labor market statistical profiles and survey reports; and qualitative and empirical studies of external labor migration by Nepalese, its determinants, and its effects. These studies suggest the relatively distinct nature and evolution of Nepal’s labor market.However, apart from a few exceptions, existing studies are largely non-empirical, weak in statistical rigor, and/or biased in terms of data representativeness and coverage of labor market aspects and issues.